Le Hellfest, arène discursive. Sociologie des festivals de musique live comme sphères publiques - Gérôme Guibert (Criminocorpus)
Because of its importance in terms of people affected or groups programmed, Hellfest, a festival of "extreme music" since 2006, has, by its magnitude, made visible heavy metal music in France, its amateurs and the cultural behaviors associated with metal scenes. Loved and invested by a minority of the population and not mainstream publicized until then, or treated in a condescending manner, the music and the metal culture changed status. Based on a corpus of 366 articles published between 2006 and 2011 by the daily newspaper Ouest France about or mentioning Hellfest, it will be shown that the event, its groups and the festival-goers appeared suspicious or dangerous, driven by irrational logic. Between 2007 and 2010 very heterogeneous points of view are confronted as for Hellfest, in a context of municipal and then regional elections. This is because, in the public arena of media confrontation, the power relations between hegemonic and subaltern counter-public conceptions change. This does not mean that the perception of metal does not remain controversial, given the transgressive representations it conveys, especially vis-à-vis religious symbols, militarists or totalitarian.